'Neglecta timonensis' gen. nov., sp. nov., a new human-associated species. (September 2016) - Bessis, S.; Ndongo, S.; Lagier, J.-C.; Raoult, D.; Fournier, P.-E.
Abstract: We herein describe the main characteristics of ' Neglecta timonensis ' strain SN17 (CSUR P2265) that was isolated from the stool of an 88-year-old woman with type 2 diabetes.